2017
DOI: 10.1038/srep45135
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state hippocampal functional networks associated with chemotherapy-induced prospective memory impairment in breast cancer survivors

Abstract: In this study, we aimed to investigate the intrinsic hippocampal functional connectivity (FC) network and its relationship with prospective memory in patients with breast cancer suffering from chemotherapy-induced cognitive impairment (CICI). Thirty-four breast cancer patients before and after adjuvant chemotherapy (CB and CC, respectively) and 31 age- and education-matched cognitively normal (CN) women were recruited and subjected to a prospective memory task and a resting-state functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 44 publications
(57 reference statements)
3
55
0
7
Order By: Relevance
“…Thereby, Chen et al (55) found decreased functional connectivity of the Dorsolateral prefrontal cortex (DLPFC) with the right hippocampus in BCP treated with tamoxifen compared to HC. Additionally, Cheng et al (57) found right hippocampus in BCP treated with tamoxifen compared to HC. Additionally, Cheng et al (57) found chemotherapy compared to HC, including not only the frontal and parietal cortex but also the precuneus, posterior cingulate cortex, and the cerebellum.…”
Section: Synthesized Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thereby, Chen et al (55) found decreased functional connectivity of the Dorsolateral prefrontal cortex (DLPFC) with the right hippocampus in BCP treated with tamoxifen compared to HC. Additionally, Cheng et al (57) found right hippocampus in BCP treated with tamoxifen compared to HC. Additionally, Cheng et al (57) found chemotherapy compared to HC, including not only the frontal and parietal cortex but also the precuneus, posterior cingulate cortex, and the cerebellum.…”
Section: Synthesized Findingsmentioning
confidence: 97%
“…Structure-and Connectivity-Related Hippocampal Changes or Differences in BCP Compared to HC All seven studies illustrated structure-and connectivityrelated hippocampal changes or differences compared to HC, including hippocampal volume loss (52-54, 56, 58), hippocampal deformation (58) as well as changes in bilateral hippocampal (57) and whole-brain functional connectivity (55). Reduced hippocampal volume was reported in most of the studies, referring mainly to the left hippocampus (53,54) and posterior regions (52,54).…”
Section: Synthesized Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research suggests that the developing brain is highly sensitive to cranial radiation (CR) and chemotherapy treatments for central nervous system cancers. Both chemotherapy and CR are linked to altered white matter microstructure (de Blank, Berman, & Fisher, ; (Deprez et al, ) Moxon‐Emre et al, ), altered hippocampal function (Cheng et al, ; Monje et al, ), and smaller hippocampal volumes (Kesler et al, ; Nagel et al, ; Riggs et al, ). Smaller hippocampal volumes after CR and chemotherapy are unrelated to smaller overall brain volumes (Riggs et al, ), suggesting that the developing hippocampus may be particularly vulnerable to treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In various previous rodent researches, evidences proving that chemobrain is related to impaired neurogenesis of hippocampus (14,15), neuroin ammation (16,17), oxidative stress, mitochondrial dysfunction (18,19), and structural damage to neurons have been cumulating. Several recent neuroimaging studies have reported reduced total volume and inward deformities in hippocampal sub elds in breast cancer patients (20,21). Hippocampus is also a key area in cognitive function such as memory formation, learning (22), spatial processing(23), memory recognition, prospective memory processing(24), etc..…”
Section: Introductionmentioning
confidence: 99%